2018
DOI: 10.1097/md.0000000000010202
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of epidural waveform for cervical epidural steroid injections confirmed with fluoroscopy

Abstract: The identification of epidural space with loss of resistance (LOR) is commonly performed. But it lacks specificity. Epidural pressure waveform analysis (EPWA) provides a simple confirmative adjunct for LOR. If the needle is located within the epidural space, measurement of the pressure at its tips shows a pulsatile waveform. Previous studies demonstrated satisfactory sensitivity and specificity of EPWA. However, success or failure of epidural injection was confirmed by the pinprick test, which is limited for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…However, with repeated observations and experience, the weak pulsatile waveforms can also be clearly identified. Indeed, in a previous paper which used a standard pressure transducer, 12 50% of patients had epidural waveform of weak oscillation, whereas in our cases the majority of the oscillations were mainly strong and easily evident, and in only 15% the waveforms were weak. However, previous studies were performed with commercially available blood pressure transducers not specifically designed for the epidural use, and therefore less sensitive to the epidural signal.…”
Section: Discussioncontrasting
confidence: 54%
“…However, with repeated observations and experience, the weak pulsatile waveforms can also be clearly identified. Indeed, in a previous paper which used a standard pressure transducer, 12 50% of patients had epidural waveform of weak oscillation, whereas in our cases the majority of the oscillations were mainly strong and easily evident, and in only 15% the waveforms were weak. However, previous studies were performed with commercially available blood pressure transducers not specifically designed for the epidural use, and therefore less sensitive to the epidural signal.…”
Section: Discussioncontrasting
confidence: 54%
“…Gaps in the ligamentum flavum and paravertebral muscles (including cysts and fascial planes) may lead to false-positive LOR. Contrast is usually administered during these situations, which may blur bony landmarks and needle tips 19 21. The incidence of false-positive LOR during cervical epidural injection using the lateral view was 20.5%–76.5% in previous studies; our previous study found this incidence of 20.6% 8 13 19 24.…”
Section: Discussionmentioning
confidence: 83%
“…In the 393 cervical interlaminar accesses, there was no dural puncture event though novice trainees were included as operators. The reported incidence of dural puncture in fluoroscopically guided cervical epidural procedures performed in the AP or lateral view was 1%–2% 9 10 21 22. Considering that spinal cord injury can cause permanent neurologic deficits,2 4 6 the aforementioned incidence rate is fairly high, as dural puncture may lead to spinal cord injury.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of pulsatile waveforms have been well documented in cervical [5], thoracic [6] [7] [8] [9] [10] and lumbar epidural space, [8] [11] and high sensitivity to reliably identify the epidural space and correct epidural positioning of needle and catheter has been reported in many studies [12].…”
Section: Introductionmentioning
confidence: 99%